2018
DOI: 10.4103/1673-5374.224379
|View full text |Cite
|
Sign up to set email alerts
|

Does combined therapy of curcumin and epigallocatechin gallate have a synergistic neuroprotective effect against spinal cord injury?

Abstract: Systematic inflammatory response after spinal cord injury (SCI) is one of the factors leading to lesion development and a profound degree of functional loss. Anti-inflammatory compounds, such as curcumin and epigallocatechin gallate (EGCG) are known for their neuroprotective effects. In this study, we investigated the effect of combined therapy of curcumin and EGCG in a rat model of acute SCI induced by balloon compression. Immediately after SCI, rats received curcumin, EGCG, curcumin + EGCG or saline [daily i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To investigate whether tan IIA treatment ameliorates learning and memory deficits in APP/PS1 mice, open-field test, Y-maze test, and MWM test were performed. The open-field test is mostly used to evaluate the exploration and anxiety-related behaviors in laboratory animals [ 31 ]. Compared with the WT group, APP/PS1 mice showed anxiety and less movement in exploring the central zone as indicated by less time spent in the center, fewer numbers of central entries, and shorter distance in the center.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether tan IIA treatment ameliorates learning and memory deficits in APP/PS1 mice, open-field test, Y-maze test, and MWM test were performed. The open-field test is mostly used to evaluate the exploration and anxiety-related behaviors in laboratory animals [ 31 ]. Compared with the WT group, APP/PS1 mice showed anxiety and less movement in exploring the central zone as indicated by less time spent in the center, fewer numbers of central entries, and shorter distance in the center.…”
Section: Resultsmentioning
confidence: 99%
“…On a mechanistic ground, these effects may be related to the polyphenols antioxidant activity (Lalkovièová and Danielisová, 2016), thus supporting the ability of such compounds and of the downstream pathways to exert neurotrophic effects (Moosavi et al, 2015). In this respect, a typical example is provided by grape seed polyphenols (GSP), whose ability to promote neural regeneration has been demonstrated in different studies (He et al, 2017; Renno et al, 2017; Ruzicka et al, 2018), as specifically shown in the case of the developmental events of cochlear hair cells (Gu et al, 2015). The polyphenol antioxidant activity may therefore represent a relevant and appropriate therapeutic tool toward the mentioned conditions (Abolhassani et al, 2017; Ahmed et al, 2017; Aguilera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The open field test measures novelty-induced locomotion and anxiety-like behavior ( Ruzicka et al, 2018 ). In this test, mice injected with shRNA-TRPC6 showed a significant increase in the distance traveled compared to mice in the shRNA-control group ( Figures 5A,B,E ), suggesting that mice injected with shRNA-TRPC6 display increased levels of novelty-induced locomotion.…”
Section: Resultsmentioning
confidence: 99%